On the analysis of property unit sales over time - Carmichael, David G.; C. A. Balatbat, Maria (International Journal of Strategic Property Management, 2012)
Investors in multiple unit developments, such as apartments, townhouses, condominiums and connected dwellings, rely on a stream of sales in order to achieve a viable cash flow, a dominant issue. At the feasibility phase of a development, sales over time are estimated, and commonly this is done deterministically. However, with uncertainty in sales, such estimates may not be realised when the market is tested, and the investor's hoped-for cash flow may not be attained. Accordingly some acknowledgment of this uncertainty should be made in order to assess the associated risks. In this light, the paper presents an analysis of sales over time where uncertainty in sales is taken into account. The underlying model developed is based on Markov chains, specifically adapted to sales. Actual development data are used to illustrate the paper's approach and conclusions. The model provides useful core information on sales, both in quantum and timing, to the investor. The model provides a tool useful to practitioners, and one complementary to their existing sales analysis approaches. The paper provides an original contribution, and one of practical use, to established investor practices in the analysis of sales of multiple unit developments.First Publish Online: 11 Jan 2012